ASSESSMENT OF GENETIC VARIABILITY, CHARACTER ASSOCIATION AND PATH ANALYSIS IN MAIZE (Zea mays L.) - B. MALLAIAH, V. SRIDHAR, G. ANUSHA, D. BHADRU, S. VANISRI, G. USHA RANI (The Journal of Research, PJTSAU, 2023)
The present investigation was conducted to estimate the genetic parameters and character association of 62 maize genotypes for eleven characters at Maize Research Centre, Rajendranagar during Rabi, 2020-21. Analysis of variance revealed the existence of significant variability among the genotypes. Among the traits studied, plant height, ear height, number of kernels per row and 100 seed weight showed moderate GCV with high heritability and high genetic advance as percent of mean. The grain yield showed a significant positive genotypic correlation coefficient with all the characters except with days to 50 % tasseling, days to 50 % silking and days to maturity. The path coefficient analysis revealed that days to 50 % tasseling, days to 50 % silking, plant height, ear height, ear length, number of kernels rows per ear, number of kernels per row and 100 seed weight exhibited positive direct effects on grain yield whereas days to maturity and ear girth showed a negative direct effect on grain yield. The selection of characters with moderate to high GCV with high heritability, high genetic advance as percent of mean and characters which shows significant positive genotypic correlation coefficient along with positive direct effect contributing towards yield playsan important role in increasing the grain yield.